Post-coital cervicovaginal injury in a thorough bred broodmare - DADARWAL, DINESH; DUGGAL, G P; GUPTA, A K; PUROHIT, G N (The Indian Journal of Animal Reproduction, 2023)
A thoroughbred broodmare suffered from lacerations in the cranial vagina during covering with a stallionand subsequently developed vaginitis. It was treated with parentral antibiotics for 3 days and dressing of thevaginal wound with Betadine solution for 14 days with an unevenful recovery.
Keywords: Post coital cervico vaginal injury; mare